Optimization of polymer inclusion membranes (PIMs) preparation for immobilization of Chrome Azurol S for optical sensing of aluminum(III) - Ngarisan N.I.; Ngah C.W.Z.C.W.; Ahmad M.; Kuswandi B. (Elsevier, 2024)
Indexed by WOS/ Scopus